Towards Conditions of philosophical innovation - Meriem Chougrani; Hocine Boudaoud (Social Empowerment Journal, 2019)
Innovation is a process of a continuous human production which aims at changing the reality, its in-time notions, its hypotheses as well as the challenges it should rise. It starts from the accumulated and accessible notions to reach its goal by use of many rectifications across history. Those rectifications deal with the depth of what the thinking being could produce to concretize a high level of awareness to make the humanity move forward. Since the process of innovation is tightly linked to the psychological side in its general tendency according to the conditions, motivations and goals defined by the physical world, the existed abstract thinking, which the philosophical thinking, its motivations as well as its final dimensions, own and require, and which is tightly linked to the whole civilizational reality and the global civilizational need that involve the innovation in multiple fields on the basis of the mind use to generate a theory that brings together the different sides of the reality so that it defines its path on the basis of the extent of the response to the problems and requirements of innovation in a particular period of time and in a precise environment.